Does osteoporosis cause pain even without a fracture? An observational study - OKÇU, MEHMET (My University, 2023)
Introduction/backgroundOsteoporotic fractures are usually painful. However, data on whether osteoporosis without fracture causes pain are insufficient. This study aims to determine whether osteoporosis without fracture is the cause of pain.MethodologyPatients aged over 18 years who visited the Physical Medicine and Rehabilitation outpatient clinic of a tertiary university hospital for dual-energy X-ray absorptiometry scan and were suitable for dual-energy X-ray absorptiometry scan without a history of fracture were included in the study. Patients with a history of fractures or those with fracture/fracture sequelae on X-rays were excluded. The cervical, lumbar, and thoracic spine and general body pains of the patients were questioned and dual-energy X-ray absorptiometry results were recorded.ResultsThe study was conducted with 139 patients. Lumbar bone mineral density and T score values of the patients were found to be negatively correlated with the numerical rating scale levels of the cervical, thoracic, lumbar spine, and general body pain. Hip total bone mineral density and T score values were also negatively correlated with numerical rating scale scores of the lumbar and thoracic spine and general body pain. When the patients were divided into two groups as those with and without osteoporosis, it was found that the cervical, lumbar, thoracic spine, and general body pain numerical rating scale levels of the patients with osteoporosis were significantly higher than the group without osteoporosis.ConclusionThe results of this study showed that osteoporosis might be associated with pain even though there is no fracture.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; İnsan Bilgisayar Etkileşimi; Fizik Bilimleri; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Human-Computer Interaction; Physical Sciences; Osteoporosis; fracture; neck pain; low back pain; back pain; pain; SYMPATHETIC INNERVATION; VERTEBRAL BODIES; DIAGNOSIS; SCALES; WOMEN